Ultrasonography and contrast-enhanced CT findings of tularemia in the neck - Serap Doğan; Afra Ekinci; Hayati Demiraslan; Ayşegül Ulu Kılıç; Ertuğrul Mavili; Mustafa Öztürk; Hakan İmamoğlu; Mehmet Doğanay (Diagnostic and Interventional Radiology, 2016)

(untitled)
PURPOSE:We aimed to evaluate the ultrasonography (US) and contrast-enhanced computed tomography (CECT) findings of tularemia in the neck.METHODS:US and CECT findings of 58 patients with serologically proven tularemia were retrospectively evaluated. Forty-eight patients underwent US and 42 patients underwent CECT. Lymph node characteristics and parotid preauricular region involvement were analyzed using US and CECT. In addition, involvement of larynx, oropharynx, and retropharynx; presence of periorbital edema; and neck abscess formation were evaluated using CECT. Fine needle aspiration cytology (FNAC) results of enlarged lymph nodes were analyzed in 29 patients.RESULTS:Hypoechoic pattern, round shape, absence of hilum, and cystic necrosis were seen in most of the lymph nodes especially at level 2 and 3 on US and CECT. Matting was more commonly observed than irregular nodal border on US and CECT. Parotid preauricular region involvement was seen in 20.8% of patients on US. Oropharyngeal, retropharyngeal, laryngeal and parotid preauricular region involvement and periorbital edema were seen in 52.4%, 19.1%, 4.8%, 31%, and 9.5% of tularemia patients, respectively. Neck abscess was found in 59.5% of patients on CECT. Suppurative inflammation was the most common finding of FNAC.CONCLUSION:Tularemia should be considered in the presence of level 2 and 3 lymph nodes with cystic necrosis, matting, absence of calcification, oropharyngeal and retropharyngeal region involvement, and neck abscess, particularly in endemic areas.